2011
DOI: 10.1007/s12230-011-9212-5
|View full text |Cite
|
Sign up to set email alerts
|

Potato Response to Nitrogen Form and Nitrification Inhibitors

Abstract: Several previous experiments where nitrification inhibitors have been used with potato have resulted in yield and/or tuber quality reductions, especially when used in combination with all-ammonium fertilizer N sources. This experiment examined the effectiveness of inhibitors over a 3-year period when used with several N sources with varying ammonium-N contents, all applied at emergence on an irrigated loamy sand in central Wisconsin. In 3 of 6 siteyears, use of an inhibitor increased total tuber yield with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The higher soil NO 3 − -N due to applying NIs might have been attributable to a higher soil NH 4 + -N ( Figures 3A and 3B), when compared to the CF plot. Later on in the growing season, a reduction in soil NO 3 − -N through crop uptake, NO 3 − leaching, and denitrification might be reasons for the minimizing the NI effect on soil NO 3 − -N, as was observed in this study and in the investigation by Kelling, Wolkowski, and Ruark (2011) after 56-57 days of fertilizer application in a potato field. However, the NI effect on soil NO 3 − -N was variable, depending on climatic conditions (Zaman et al 2009) and N fertilizer, for example, the application rate (Martin et al 1997).…”
Section: Soil No 3 − -Nsupporting
confidence: 59%
See 2 more Smart Citations
“…The higher soil NO 3 − -N due to applying NIs might have been attributable to a higher soil NH 4 + -N ( Figures 3A and 3B), when compared to the CF plot. Later on in the growing season, a reduction in soil NO 3 − -N through crop uptake, NO 3 − leaching, and denitrification might be reasons for the minimizing the NI effect on soil NO 3 − -N, as was observed in this study and in the investigation by Kelling, Wolkowski, and Ruark (2011) after 56-57 days of fertilizer application in a potato field. However, the NI effect on soil NO 3 − -N was variable, depending on climatic conditions (Zaman et al 2009) and N fertilizer, for example, the application rate (Martin et al 1997).…”
Section: Soil No 3 − -Nsupporting
confidence: 59%
“…The studied NIs have a suppressive effect on soil nitrification, because (1) DCD inhibits cytochrome oxidase and decreases the oxidation of NH 4 + to NO 2 − (Di and Cameron 2002) and (2) neem oil contains meliacins that can reduce soil nitrifier activity (Kiran and Patra 2003;Kumar et al 2007 (Martin et al 1997;Kumar et al 2007;Matsushima, Choi, and Inubushi 2009). In a potato field, DCD was effective in slowing nitrification and the soil had a higher soil NH 4 + -N than the applied urea-NH 4 NO 3 with no DCD (Kelling, Wolkowski, and Ruark 2011). Furthermore, Wadman, Neeteson, and Wijnen (1993) found that in potato fields, the use of DCD with a slurry application in late autumn increased soil NH 4 + -N in the upper soil layer compared to that without DCD.…”
Section: Soil Nh 4 + -Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelling et al (2011) found similar specific gravity values when AN, liquid urea ammonium nitrate, and a 50:50 combination of urea and AS were applied, however Sanderson and White (1987) reported that specific gravity was lower with urea than AN. Contrary to our findings, other studies found a greater quantity of culls when a higher proportion of the N applied was in NH 4 than NO 3 form (Bundy et al, 1986; Kelling et al, 2011). This phenomenon was attributed to NH 4 –induced water stress since crops receiving NH 4 tend to exhibit reduced water uptake (Hendrickson et al, 1978).…”
Section: Discussionmentioning
confidence: 88%
“…It is well known that most plant species have a preference for NO 3 − than NH 4 + . Moreover, some studies showed that plants supplied with both NO 3 − and NH 4 + may be more productive than those supplied with either form alone (Cao and Tibbitts, 1993, 1998; Kelling et al, 2011). Hence, the overall greater plant N accumulation and ANR for AN than AS may be due in part to the presence of both forms on N supplied by AN.…”
Section: Discussionmentioning
confidence: 99%